CRISPR-UnLOCK: Multipurpose Cas9-Based Strategies for Conversion of Yeast Libraries and Strains - Roggenkamp, Emily; Giersch, Rachael M.; Wedeman, Emily; Eaton, Muriel; Turnquist, Emily; Schrock, Madison N.; Alkotami, Linah; Jirakittisonthon, Thitikan; Schluter-Pascua, Samantha E.; Bayne, Gareth H.; Wasko, Cory; Halloran, Megan; et al. (Frontiers in Microbiology, 2017)
Saccharomyces cerevisiae continues to serve as a powerful model system for both basic biological research and industrial application. The development of genome-wide collections of individually manipulated strains (libraries) has allowed for high-throughput genetic screens and an emerging global view of this single-celled Eukaryote. The success of strain construction has relied on the innate ability of budding yeast to accept foreign DNA and perform homologous recombination, allowing for efficient plasmid construction (in vivo) and integration of desired sequences into the genome. The development of molecular toolkits and “integration cassettes” have provided fungal systems with a collection of strategies for tagging, deleting, or over-expressing target genes; typically, these consist of a C-terminal tag (epitope or fluorescent protein), a universal terminator sequence, and a selectable marker cassette to allow for convenient screening. However, there are logistical and technical obstacles to using these traditional genetic modules for complex strain construction (manipulation of many genomic targets in a single cell) or for the generation of entire genome-wide libraries. The recent introduction of the CRISPR/Cas gene editing technology has provided a powerful methodology for multiplexed editing in many biological systems including yeast. We have developed four distinct uses of the CRISPR biotechnology to generate yeast strains that utilizes the conversion of existing, commonly-used yeast libraries or strains. We present Cas9-based, marker-less methodologies for (i) N-terminal tagging, (ii) C-terminally tagging yeast genes with 18 unique fusions, (iii) conversion of fluorescently-tagged strains into newly engineered (or codon optimized) variants, and finally, (iv) use of a Cas9 “gene drive” system to rapidly achieve a homozygous state for a hypomorphic query allele in a diploid strain. These CRISPR-based methods demonstrate use of targeting universal sequences previously introduced into a genome.